Efisiensi Tegangan Dan Ukuran Gear Terhadap Konsumsi Daya Motor DC Pada Mobil Listrik Ken Dedes - Ahmad Raihan Hafizh; Nike Nur Farida (Jurnal Kendali Teknik dan Sains, 2025)
The use of fossil-fueled vehicles has long been a major cause of exhaust emissions that pollute the air and exacerbate global climate change. In an effort to address this problem, Indonesia has begun developing electric vehicles as a more environmentally friendly alternative solution. Electric vehicles (EVs) are considered capable of reducing dependence on fossil fuels while simultaneously reducing air pollution levels. The Indonesian government has demonstrated its commitment to supporting electric vehicle development by issuing several strategic policies, including Presidential Regulation (Perpres) Number 55 of 2019 concerning the Acceleration of the Battery-Based Electric Motor Vehicle Program for Road Transportation, and Presidential Instruction (Inpres) Number 7 of 2022 concerning the Use of Battery-Based Electric Motor Vehicles as official vehicles for central and regional government agencies. In line with these policies, research was conducted to assess the power consumption efficiency of the Ken Dedes electric vehicle prototype, designed using a 250-watt DC motor and a mid-drive system. The main focus of this research was to analyze the effect of variations in module input voltage and gear size on the vehicle's power consumption level. The method used was an experimental approach with a quantitative approach, where a series of tests were conducted on several gear combinations and input voltage levels. The results of the study indicate that variations in these two parameters—gear size and input voltage—significantly affect motor power consumption. The most optimal combination in this study achieved a power consumption efficiency of 6 Wh/km. This figure demonstrates the most energy-efficient performance in vehicle operation and can serve as a benchmark for further development of similar electric vehicles. This research provides an important contribution to efforts to encourage the use of more efficient and sustainable electric vehicles in Indonesia.